2023
DOI: 10.1002/jmv.28880
|View full text |Cite
|
Sign up to set email alerts
|

The causal role of gut microbiota in susceptibility and severity of COVID‐19: A bidirectional Mendelian randomization study

Abstract: Growing evidence has shown that altered gut microbiota is associated with the pathogenesis of COVID‐19, but their causal effects are still unclear. We conducted a bidirectional Mendelian randomization (MR) study to assess the causal effects of gut microbiota on COVID‐19 susceptibility or severity, and vice versa. The microbiome genome‐wide association studies (GWAS) data of 18 340 individuals and GWAS statistics from the COVID‐19 host genetics initiative (38 984 European patients and 1 644 784 controls) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Of particular interest, a bidirectional Mendelian randomization study suggests that Alloprevotella may increase COVID-19 susceptibility, while SARS-CoV-2 infection causally leads to the depletion of the Lachnospiraceae family. 42 To predict the potential roles of these altered bacterial species in regulating hyperinflammatory responses to SARS-CoV-2 infection, Spearman's correlation analysis was conducted. Notably, Lachnospiraceae_NK4A136_group and unclassified_f_ Lachnospiraceae are speculated to have anti-inflammatory effects based on experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, a bidirectional Mendelian randomization study suggests that Alloprevotella may increase COVID-19 susceptibility, while SARS-CoV-2 infection causally leads to the depletion of the Lachnospiraceae family. 42 To predict the potential roles of these altered bacterial species in regulating hyperinflammatory responses to SARS-CoV-2 infection, Spearman's correlation analysis was conducted. Notably, Lachnospiraceae_NK4A136_group and unclassified_f_ Lachnospiraceae are speculated to have anti-inflammatory effects based on experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified a causal association between three gut microbiota, namely Parasutterella, Dorea, and Lachnoclostridium, and PTB. Notably, Parasutterella has been found to have a causal relationship with various other conditions in several Mendelian randomization studies, including COVID-19 ( Chen H. et al, 2023 ), intrahepatic cholangiocarcinoma (ICC) ( Chen Z. et al, 2023 ), chronic kidney disease (CKD) ( Ren et al, 2023 ), and prostatitis ( Shen et al, 2024 ). Meanwhile, Dorea is associated with autism spectrum disorder (ASD) ( Li Z. et al, 2023 ), inflammatory bowel disease (IBD) ( Zhang et al, 2021 ), hypertensive disorders in pregnancy (HDP) ( Wu et al, 2023a ), polycystic ovary syndrome (PCOS) ( Min et al, 2023 ), hemorrhagic stroke ( Shen et al, 2023 ), age-related macular degeneration (AMD) ( Li and Lu, 2023 ), nicotine dependence ( Chen Y. et al, 2023 ), and insomnia ( Li Z. et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the gut microbiota may have a causal relationship with the severity of COVID‐19, thus providing new evidence and ideas for the study of the pathogenesis of SARS‐CoV‐2 mediated by gut microbiota. 107 , 108 …”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%